Voice rehabilitation after total laryngectomy with the infrahyoid musculocutaneous flap. (1st April 2021) - Li, Changjiang; Fang, Yi; Wu, Haitao; Shu, Min; Cheng, Lei; He, Peijie
Abstract: Background: It is important for the patients to reconstruct the voice phonic function by surgery after total laryngectomy in the developing countries. Aims/Objectives: To investigate the clinical outcomes of voice reconstruction using an infrahyoid musculocutaneous flap for patients after total laryngectomies. Materials and methods: Eighteen male patients recruited were laryngectomized. The infrahyoid musculocutaneous flap was designed. After total laryngectomy, the lower edge of the flap was sewed with the upper edge of the tracheostomy opening. Next, the lateral and medial edges of the flap were anastomosed to create a pronunciation tube. Finally, the remaining opening of the tube was sutured with the anterolateral wall of the hypopharynx to establish a communication with the pharyngeal cavity. Results: A total of 17 cases of flaps were survived and only 1 necrosed. There were 17 patients without serious complications, except that 6 cases had mild irritable cough when gulping water. However, it could be relieved through blocking tracheostoma. One year after operation, all patients could more remarkably articulate clear, powerful, and consistent words. The articulatory configuration was existed under rigid laryngoscope and CT. Conclusions and significance: The use of an infrahyoid myocutaneous flap is feasible for the voice restoration in the patients undergoing total laryngectomy.